Recent advances in the management of neuropsychiatric symptoms in dementia - Forlenza, Orestes V.; Loureiro, Jï¿½lia Cunha; Pais, Marcos Vasconcelos; Stella, Florindo [UNESP] (My University, 2017)
Purpose of review The present article addresses intriguing questions related to the clinical intervention in distinct neuropsychiatric syndromes of patients with dementia. Recent findings We reviewed 154 articles published between 2015 and 2016 targeting psychopharmacological and nonpharmacological interventions, and safety-tolerability concerns. We selected 115 articles addressing the purpose of this study. Of these, 33 were chosen because they were dedicated to subtopics: agitation (42), depression (33), apathy (18), sleep disorders/anxiety (8), and psychosis (4). Clinical studies using both pharmacological (70) and nonpharmacological (37) interventions were considered; others were included for theoretical support. Regarding the methodological design, we found double-blind RCTs (17), single-blinded RCTs (4), open-label studies (18), case reports (5), cross-sectional or cohort studies (25), epidemiological papers (2), and expert reviews (44). This observation raises concerns about the overall methodological adequacy of a substantial proportion of studies in this field, which limits the potential of generalization of the findings. Finally, 18 studies were designed to determine safety-tolerability issues of psychotropic medications (6 were discussed). Summary Effective and well tolerated treatment of neuropsychiatric syndromes in dementia remains a critically unsolved challenge. We understand that this is an extremely important area of research, and critically required to guide clinical decisions in geriatric neuropsychiatry.
Keywords: Behavioral and psychological symptoms of dementia; Cognition; Dementia; Neuropsychiatric symptoms; Nonpharmacological interventions; Pharmacological management